Oil Resource Dependence, Financial Sector Development and Sectoral Performance in Nigeria - Oderinde, L. Oladele; Olusoji, Modinat O. (NIU Journal of Social Sciences, 2020)
This study examined the impact of oil resource dependence on the relationship between financial sector development and economic growth in Nigeria and explores whether the effect differ among key sectors of the economy. Time series econometrics analysis anchored on an aggregate production function theoretical framework of the augmented Solow’s model is employed for the period 1981-2016. The study used a more robust measure of oil dependency. The effect of financial development when account is taken of oil dependence is negative in both manufacturing and agriculture sector but positive in the service sector and in the aggregate economy. This supports the hypothesis that oil resource dependency influences the finance-growth nexus in Nigeria with varied impact on the key sectors. Keywords: Dutch Disease, financial sector, sectoral performance